Pengaruh kompetensi auditor independen dan tekanan anggaran waktu terhadap pendeteksian fraud - Presti Rosiana; Indra Mahardika Putra; Yopie Aprianto Setiawan (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2019)
This study aims to examine the effect of independent auditor competencies and time budget pressures on fraud detection. The population of this study is the auditors in the Jakarta area. Data collection in this study uses the survey method. Statistical testing uses multiple linear regression analysis with a significance level of 5%. The type of research used is quantitative by using a population of auditors working at the Public Accounting Firm (KAP) in DKI Jakarta. Data is obtained by distributing questionnaires to auditors who meet the criteria. The results of this study, it can be concluded that Auditor Competency has an effect on Fraud Detection, but Time Budget Pressure has no effect on Fraud Detection.